RETRACTION Setyawan, H., Suyanto, S., Ngatman, N., Purwanto, S., Suyato, S., Darmawan, A., Shidiq, A. A. P., Eken, Özgür, Pavlovic, R., Latino, F., Tafuri, F., Wijanarko, T., Ermawati. S, E. S., & Gusliana HB, G. H. (2024). El efecto de la implementación de material de tiro con arco de gestión de clases de educación física para mejorar la concentración de los estudiantes de primaria (The Effect Of Implementing Physical Education Class Management Archery Material To Improve Concentration Elementary School Students). Retos, 56, 879–886. https://doi.org/10.47197/retos.v56.105216 - RETOS, RETOS (Retos, 2025)
Setyawan, H., Suyanto, S., Ngatman, N., Purwanto, S., Suyato, S., Darmawan, A., Shidiq, A. A. P., Eken, Özgür, Pavlovic, R., Latino, F., Tafuri, F., Wijanarko, T., Ermawati. S, E. S., & Gusliana HB, G. H. (2024). El efecto de la implementación de material de tiro con arco de gestión de clases de educación física para mejorar la concentración de los estudiantes de primaria (The Effect Of Implementing Physical Education Class Management Archery Material To Improve Concentration Elementary School Students). Retos, 56, 879–886. https://doi.org/10.47197/retos.v56.105216Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 12Authors in the published PDF with modified authors: 14Differences between the authors between both moments: +7 y -5 (Additions: Ngatman, Sugeng Purwanto, Suyato, Ratko Pavlovic, Tiok Wijanarko, Gusliana HB, Ermawati. S. Eliminated: Suharjana, Sumaryanto, José Vicente García-Jiménez, Nuridin Widya Pranoto, Muhammad Imam Rahmatullah)